Resource acquisition method based on instant messaging application and related device - PAN YUANYU; ZHU BIAOYI; HUANG TIEMING; LIU XIALU; LI BIN; LI BINGJIAN; HUANG JIAXIN (2024)
The invention discloses a resource acquisition method based on an instant messaging application and a related device, and the method comprises the steps: receiving an application adding message used for providing an application adding entrance through a first account, so as to guide a first main member to get the use authority of a resource application; when an application adding entry is displayed on a message interface of a first account, a first main member can execute a first trigger operation on the application adding entry to enter an application adding interface of a resource application. After the first subject member executes the adding operation on the application adding interface, the resource application can be added to the working table in the first instant messaging application, and receiving of the use permission of the resource application is completed, so that the second subject member in the target subject can obtain the resource through the resource application in the working table. The sec